Coordinated bidirectional charging of multiple types of electric vehicles: A risk-based model - Omid Sadeghian; Behnam Mohammadi-Ivatloo (International Journal of Electrical Power & Energy Systems)
This paper investigates the bidirectional charging management of distributed parking lots accommodating multiple types of electric vehicles (EVs). The distribution of each EV type accross parking lots is determined based on various factors such as the proportion of EV types at specific load points, the EV penetration rate, peak demand at related load points, the residential load share, and the average household consumption. An 18-bus microgrid containing 8376 EVs of six types is analyzed using a stochastic programming model that incorporates uncertainties in load demand, electricity price, renewable sources, and EV energy usage. The proposed model accounts for power losses in the grid-connected microgrid via an approximate power flow model. Risk management significantly reduces the economic risk of the worst-case scenario by around 20%, while flexible loads reduce carbon emissions by about 10.5% and the expected cost by roughly 4%. Additionally, increasing the willingness rate of EV owners to discharge their vehicles contributes to an additional 2.3% reduction in expected costs. Findings highlight the model’s capability to effectively manage bidirectional charging scheduling for diverse EV types, offering a practical solution for real-world systems facing complex technical and economic challenges.